Early childhood literacy teachers in high poverty schools : a study of courage and caring - Landa, Melissa Hare (Lanham, Maryland : Lexington Books, 2018)
Much has been written about the failure of White American public school teachers to effectively teach low-income children of color to read and write. Scholars have offered numerous explanations for this failure, including the reluctance of teacher preparation programs to address cultural competence and the lack of cultural diversity among teacher educators. In response to reported failures such as high attrition rates of novice teachers and low test scores, American public schools are being subjected to increased standardization of the curriculum and high stakes testing. This book provides rich illustrations of White early literacy teachers who choose to remain in low-income school communities, where they effectively and passionately embrace their students, families, and communities. Blending the teachers' successful practices, shown in in-depth interviews excavating their identities and life experiences, with theoretical frameworks about teaching and learning, Early Childhood Literacy Teachers in High Poverty Schools: A Study of Boundary Crossing discusses the responsibility of public educators to cross geographical, economic, and political divisions on behalf of their students, and offers strategies for teacher educators to equip future teachers for these tasks. -- Provided by publisher.
Choices: the Roots of Action -- Voices in the Classroom -- Weaving a Tapestry of Human Identity -- Stepping over Boundaries -- Following the Equity Trail: A Kaleidoscope of Learning.
Includes bibliographical references and index.
Keywords: Language arts (Early childhood) -- United States; Poor children -- Education (Early childhood) -- United States; Children of minorities -- Education (Early childhood) -- United States; Teachers, White -- United States